Monitoring data collection templates for AgriLAC Initiative - Reyes, Byron A.; Vargas Gonzalez, Sandra Marcela; Espada Castro, Andres David; Gardeazábal Monsalve, Andrea (2022)
This is the first generation (2022) of data collection templates to collect monitoring data for AgriLAC. These templates will evolve over time, to make them more practical and accurate to respond to the Initiative needs. The document was prepared to use directly, or to program to use with a data collection software.